TAFSIR AYAT TENTANG PRODUKSI DALAM EKONOMI SYARIAH - Sya’idun Sya’idun (Investama : Jurnal Ekonomi dan Bisnis, 2022)
Production is a process that has existed on Earth since humans first inhabited it. the word production in Arabic with the word